2014
DOI: 10.1209/0295-5075/105/56003
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous effect of hydrogenation on phonon thermal conductivity in thin silicon nanowires

Abstract: Using equilibrium molecular-dynamics simulations, we investigate the phonon thermal conductivity of hydrogenated silicon nanowires (H-SiNWs). In contrast to the usual thermal conductivity reduction observed upon surface passivation due to the enhancement of phonon-surface scattering in nanostructures, we observe increased thermal conductivity upon the surface hydrogenation of thin SiNWs as compared to pure SiNWs. We show that such an anomalous effect arises mainly from the hydrogenation-induced specific change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…The PDOS of the perforated film and the crystalline film are close, while the PDOS of the amorphous film and amorphous perforated film are close. For the crystalline film, in accordance with previous studies [ 51 ], there is a strong peak at high frequency of 17 THz and a weak peak at low frequency of 5 THz. For the perforated silicon film, the reduction of atoms in the perforated region leads to a decrease in the peak and a shift to the left.…”
Section: Resultssupporting
confidence: 91%
“…The PDOS of the perforated film and the crystalline film are close, while the PDOS of the amorphous film and amorphous perforated film are close. For the crystalline film, in accordance with previous studies [ 51 ], there is a strong peak at high frequency of 17 THz and a weak peak at low frequency of 5 THz. For the perforated silicon film, the reduction of atoms in the perforated region leads to a decrease in the peak and a shift to the left.…”
Section: Resultssupporting
confidence: 91%
“…Figure 7 shows the PDOS of the crystalline silicon film and the thermal cloak. For the crystalline silicon film, consistent with a previous study [65], a weak and a strong peak appeared at 5 THz and 17 THz, respectively. Phonons are generated due to the excitation of atomic vibration.…”
Section: Analysis Of Cloaking Mechanism Of Nanocloaksupporting
confidence: 91%
“…4(a) that at a temperature of 100 K, the phonon PDOS of silicene and silicon is mainly distributed in the region of 0-20 THz, which is the same as that reported in previous studies. [42][43][44] Since the phonon frequency does not depend on the amplitude of the oscillations, the PDOS of harmonic systems should be temperature-independent. However, when the temperature increases to 400 K, it is observed that both the PDOS of silicene and a-Si become broader, which indicates that the umklapp scattering mechanism is dominant at this temperature range and the phonon anharmonicity is significant.…”
Section: Calculatedmentioning
confidence: 99%